The application of serum N-MID in auxiliary diagnosis and therapeutic effect monitoring of bone metastasis in patients with primary lung cancer - LU Li, LU Renquan, SUN Jiajun, LU Ning, GUO Lin (Zhongguo aizheng zazhi, 2021)
Background and purpose: There is a lack of serum markers for the diagnosis of bone metastasis in patients with primary lung cancer currently. This study aimed to explore the expression level of serum N-terminal mid-fragment (N-MID) of osteocalcin (OC) and its functions in the diagnosis and therapy monitoring of bone metastasis in patients with lung cancer. Methods: A total of 231 patients with clinically classified primary lung cancer in Fudan University Shanghai Cancer Centre from March 2017 to February 2018 were enrolled as the experimental group, including 97 patients with bone metastasis and 134 without bone metastasis. Sixty-nine healthy adults without cancer were included in the same period as the healthy control group. Serum levels of N-MID, carcinoembryonic antigen (CEA), neuron-specific enolase (NSE), cytokeratin 19 fragment (CYFRA21-1) and alkaline phosphatase (ALP) were measured. The correlation with clinical characteristics of bone metastasis in lung cancer was analyzed by using multivariate logistic regression analysis. Results: Expression levels of N-MID before treatment were significantly higher in the bone metastasis group than in the group without bone metastasis (P ＜ 0.001) and healthy control group (P ＜ 0.001). According to the results of multivariate logistic regression analysis, the serum levels of N-MID (OR=9.265) and NSE (OR=2.688) were risk factors of bone metastasis in lung cancer patients. The cut-off level of serum N-MID was determined as 14.96ng/mL by the receiver operating characteristic (ROC) curve, and the experimental group was divided into two subgroups. The progression-free survival (PFS) of lung cancer patients whose serum N-MID levels were higher than 14.96ng/mL before treatment was significantly lower than that of patients with N-MID level lower than 14.96ng/mL (HR=2.040). In lung cancer patients with bone metastasis, the decrease of serum N-MID level after treatment indicated remission (P ＜ 0.001). Conclusion: The serum level of N-MID is closely correlated to the bone metastasis in lung cancer. The detection of serum N-MID before and after treatment can be applied in both auxiliary diagnosis and monitoring therapeutic effect in lung cancer patients with bone metastasis.